ANALYSIS OF DISTRIBUTION OF THE DIRECT CASH ASSISTANCE (BLT) PROGRAM IN TANJUNG VILLAGE, KOTO KAMPAR HULU DISTRICT, KAMPAR DISTRICT - Rahmah, Sitti; Riski, Muhammad (Sultan Syarif Kasim State Islamic University, Riau, 2024)
This research was conducted in Tanjung Village, Koto Kampar Hulu District, Kampar Regency. The aim of this research is to determine the distribution and obstacles in the Direct Cash Assistance (BLT) Program in Tanjung Village, Koto Kampar Hulu District, Kampar Regency. Data obtained from this research was through observation, interviews and documentation studies. Based on the research conducted, it was found that the village head initially held a village meeting regarding the names of the heads of families who would receive assistance. Furthermore, there were complaints from the public regarding the names of family heads who were entitled to receive aid. Distribution of the BLT program is carried out in accordance with the agreed data collection stages. The obstacles faced in the distribution of the Direct Cash Assistance (BLT) Program in Tanjung Village, Koto Kampar Hulu District, Kampar Regency are that data collection on recipient communities is still not on target, because it is based on the names of the closest people proposed by village officials and does not pay attention to the community. the less fortunate who have not received assistance such as: BLT, PKH, Raskin and other social assistance.